Factors Associated With Birth On Site Selection Nias Regency: Factors Associated With Birth On Site Selection Nias Regency - Dina Hura (Journal of Midwifery and Nursing, 2020)
Every day, Approximately 830 women die from preventable causes related to pregnancy and childbirth. Maternal mortality is higher in women living rural areas and among poorer communities. The main factors causing maternal mortality are the selection of places and facilities as well as birth attendant. Various Efforts have been made to reduce maternal mortality. The purpose of this was to analyze the factors influences with the decision making in the selection of delivery places. Study design using cross-sectional method with Chi square test and logistic regression. The second phase, in-depth interviews in the mother of birth, village midwiife, midwife coordinator, coach village, village head, and head of clinic. The study was conducted from September to October 2017. Research results Showed that the factor of family habits (previous experience),have an effect on to decision making in maternity election (p <0.005). The most dominant factor is family Influencing habits.